Computer-Assisted Literacy Education Serves as Intervention for Incarcerated Women. - Gannon, Marcia; Lapham, Michele (Corrections Today, 2010)
The article reports on computer-assisted literacy education for female prisoners. The practical benefits of literacy programs such as being prepared to complete the General Education Development (GED) test are mentioned. The purpose and structure of the reading laboratory curriculum in literacy education is discussed. Family outreach opportunities related to literacy programs are noted. The positive effect of literacy and GED credentials on reducing recidivism is noted.